PERBANDINGAN KEMAMPUAN BERFIKIR KRITIS SISWA DENGAN MENGGUNAKAN MODEL PEMBELAJARAN KOOPRATIF TIPE THINK PAIR SHARE DAN TIPE PROBING PROMPTING PADA MATA PELAJARAN EKONOMI - Wiwin Nur Puspitasari; Yon Rizal; Rahmah Dianti Putri (FKIP Universitas Lampung, 2019)
The aim of this research was to find out the comparison of students' critical thinking skill by using cooperative learning model between think pair share type and probing prompting type on economics subjects. This research used quasi-experimental research design with comparative approach. The population of this research was the eleventh grade students of SMA Negeri 3 Bandar Lampung in the academic year of 2019/2020. The research took two classes as the sample and they were XI IPS 1 and XI IPS 2 which consisted of 56 students. The sample of this research used a saturated sample which means that the sample was taken from the entire population of 56 students. An observation, interview, documentation and test of students’ critical thinking skill were administered to collect the data. The data were analyzed by using independent two sample t-test and an analysis of the effectiveness of the learning model (NGain). The result of this research showed that the thitung ttabel (12,376 2,005). It means that there was a significant difference of the students' critical thinking skill between students were taught by using learning model of think pair share type and students were taught by using learning model of probing prompting type.